Usability testing a web application to support evidence-based commissioning decisions for implementing mobile stroke units - Lisa Moseley; Anna Laws; Michael Allen; Gary A. Ford; Martin James; Stephen McCarthy; Graham McClelland; Laura J. Park; Kerry Pearn; Daniel Phillips; Christopher Price; Lisa Shaw; et al. (npj Digital Medicine)
Abstract Commissioning of innovations in healthcare is a complex socio-technical process, ideally informed by high quality evidence. However, evidence is not always prepared and presented in a format usable for commissioning decisions. Agile methodology, combined with qualitative co-design, were used to develop a digital web application incorporating machine learning models of stroke outcomes to inform commissioning decisions for the implementation of mobile stroke units (MSUs) in England, followed by usability testing using think aloud methodology. Sixteen stakeholders involved in developing consensus on model parameters and pathways participated with data thematically analysed. Required improvements to the web application were identified and novel insights into the complexity of context-specific commissioning decisions were generated, which also informed participants’ views on the viability of MSUs. This study provides empirical evidence in support of developing innovative and accessible digital dissemination methods to engage with commissioning processes and prospectively understand commissioning challenges.